Case report: ultrasound assisted catheter directed thrombolysis of an embolic partial occlusion of the superior mesenteric artery - Bongiovanni, Simone; Bozzolo, Marco; Amabile, Simone; Peano, Enrico; Balderi, Alberto (Frontiers in Radiology, 2023)
Acute mesenteric ischemia (AMI) is a severe medical condition defined by insufficient vascular supply to the small bowel through mesenteric vessels, resulting in necrosis and eventual gangrene of bowel walls. We present the case of a 64-year-old man with recrudescence of prolonged epigastric pain at rest of few hours duration, cold sweating and episodes of vomiting. A computed tomography scan of his abdomen revealed multiple filling defects in the mid-distal part of the superior mesenteric artery (SMA) and the proximal part of jejunal branches, associated with small intestine walls thickening, suggesting SMA thromboembolism and initial intestinal ischemia. Considering the absence of signs of peritonitis at the abdominal examination and the presence of multiple arterial emboli was decided to perform an endovascular treatment with ultrasound assisted catheter-directed thrombolysis with EkoSonic Endovascular System - EKOS, which resulted in complete dissolution of the multiple emboli and improved blood flow into the intestine wall. The day after the procedure the patient’s pain improved significantly and five days after he was discharged home asymptomatic on warfarin anticoagulation. After one year of follow-up the patient is fine with no further episodes of mesenteric ischemia or other embolisms.